(untitled) (Journal of the College of Education for Women, 2019)
Education is one of the most important topics that researcher educator and educationalsociety as a whole operated in the latter half of the twentieth century, which won thereflection and study many of officials in the educational cocked in the global regionally andtook educational systems around the world interested in the dimensions of this aspect andplanning to achieve the principle and characteristics in order to be in concerned with the individual to provide an opportunity for education and training.Experiments have been taken from this type of education in the world, including thedeveloping world snd Islam was still taken on taking science life for the rest of the humansons and on this basis, we find that studies and research took strong principle to keep theindividual and human ignorance and illiteracy to prosecute evolution and techniquesimposed on it today and in the future.Many Research studies have focused on studying foreducation in terms of policy and programmed method and it’s concept and its fields andconstraints for students in community ,schools and kindergartens exclusively.It also contributed to education in broad cast artistic culture among children. As a workvery much beneficial. and adopted the duty on it .Nabil and commitment toward society andhuman .the value and properties .Fiqimtart education and Swabath , Kamann an in the searchdo not complain about the complexity and concavity. Nor Bghos in details ?And a steadydrumbeat of various theories or condractories .a shelters also divers and inclusive for all allpsychological revelation received by the mind of a child the portrayal in the drawings areoften expressed in words as well as drawings in deliver the idea that recipient cannot beembodied by his drawings of simple and expressive colour..This is taken into consideration in this research as well as it covers many fields andbenefits researchers in this field.Therefore, the current research is trying to take a closer look at the psychologicalimplications in children’s drawings in the nursery. The first chapter came defined theimportance of research and the need for it as well as the research problem after placing thefollowing objectives:Research ObjectivesThe research aims to identify ..1.identify the children’s drawings in kindergartenageof4_6years.2. To identify the topics that kids resolve and draw most important things to focus in theirdrawings.3.psychological effect and impression left by the societies in children’s thinking throughexpression with graphics in the nursery.4.psychological revelations through children’s drawingsandby themes that were given tothem.Border researchIs determined by the current search1.objective limits: includes general philosophy of children’s drawings from the face of thescientific review.2.Spatial Order: include kindergarten eligibility birds of paradise in Zafaranyia /Baghdadarea.3.temporal limits :the academic year2013-2014The Second chapter, including previous st and philosophical framework and monetaryresearch.While chap III procedures. Chapter IV contains the conclusion and recommendationproposals of Arab and foreign sources and result relied upon by the current research as wellas summary of the Arabic language and a summary in English.